Flexural Behavior of Pre-Tensioned Precast High-Performance Steel-Fiber-Reinforced Concrete Girder Without Conventional Reinforcement: Full-Scale Test and FE Modeling - Ling Kang; Haiyun Zou; Tingmin Mu; Feifei Pei; Haoyuan Bai (Buildings)
In contrast to brittle normal-strength concrete (NSC), high-performance steel-fiber-reinforced concrete (HPSFRC) provides better tensile and shear resistance, enabling enhanced bridge girder design. To achieve a balance between cost efficiency and quality, reducing conventional reinforcement is a viable cost-saving strategy. This study focused on the flexural behavior of a type of pre-tensioned precast HPSFRC girder without longitudinal and shear reinforcement. This type of girder consists of HPSFRC and prestressed steel strands, balancing structural performance, fabrication convenience, and cost-effectiveness. A 30.0 m full-scale girder was randomly selected from the prefabrication factory and tested through a four-point bending test. The failure mode, load–deflection relationship, and strain distribution were investigated. The experimental results demonstrated that the girder exhibited ductile deflection-hardening behavior (47% progressive increase in load after the first crack), extensive cracking patterns, and large total deflection (1/86 of effective span length), meeting both the serviceability and ultimate limit state design requirements. To complement the experimental results, a nonlinear finite element model (FEM) was developed and validated against the test data. The flexural capacity predicted by the FEM had a marginal 0.8% difference from the test result, and the predicted load–deflection curve, crack distribution, and load–strain curve were in adequate agreement with the test outcomes, demonstrating reliability of the FEM in predicting the flexural behavior of the girder. Based on the FEM, parametric analysis was conducted to investigate the effects of key parameters, namely concrete tensile strength, concrete compressive strength, and prestress level, on the flexural responses of the girder. Eventually, design recommendations and future studies were suggested.